"Dois tiros nas redações": jornalismo brasileiro e o caso Pimenta Neves como incidente crítico - Carvalho, Eleonora de Magalhães (2010)
This dissertation discusses the murder of journalist Sandra Gomide by Pimenta Neves, also a journalist and her former boyfriend and boss, as a critical incident that obliged journalists covering the case to discuss and renegotiate the proper methods of work. By doing so the journalists discussed the issue of the necessary distance for covering the case in an objective way. The empirical corpus of analysis includes Folha Online reporting and texts discussed in media criticism site Observatório da Imprensa. It argues that this critical incident has mobilized a significant debate about the norms and behaviour appropriate to newsmaking, as well the power relations into the newsrooms. The ultimate purpose of the dissertation is to understand how the journalists dealt with the dilemmas presented by the case, and which measures they took in order to reinforce their interpretative authority, both inside and outside the limits of the journalists' community.